ANALISIS BEBAN KERJA DENGAN METODE FULL TIME EQUIVALENT (FTE) UNTUK MENGOPTIMALKAN JUMLAH PEGAWAI TIM PLTA X - Wahyu Maulana (2022)
PLTA X is a hydroelectric power plant located in North Sumatra. In carrying out its production process, PLTA X is experiencing problems, namely the optimal work pattern that has not been created, the high number of overtime, and the limited maintenance team, causing the maintenance process to require more time. The length of the maintenance process has resulted in the production target not being achieved due to a shortage of employees (manpower) and an uneven workload at PLTA X. For this reason, it is necessary to measure workload as a basis for calculating workforce requirements. In this study, researchers used the Full Time Equivalent (FTE) method. After obtaining the FTE calculation results for each PLTA X position, it is known that Support & Finance, Adm. Warehouse Staff, CSR/Humas Staff, and Security are included in the FTE underload index category. Plant Manager, Driver, House Keeping, DANRU Security are included in the FTE fit index category. Spv. Operations, Spv. Maintenance, HSE Spv, Bendung Operators, Power House Operators, Headpond Operators, Mechanical Technicians, and Electrical Technicians are included in the FTE overload index category. Proposed improvements in the form of adding 1 Power House Operator employee, 1 Mechanical Technician employee, and 1 Electrical Technician employee. In addition, there was also a reduction of 1 CSR/PR staff employee and a delegation of activities to equalize the workload